2017
DOI: 10.1111/trf.14383
|View full text |Cite
|
Sign up to set email alerts
|

Nonhemolytic passenger lymphocyte syndrome

Abstract: Focusing on hemolysis, without a comparable effort to detect donor-derived antibodies diverts from the primary pathophysiology of PLS and limits capturing the full scope of the syndrome. Recognition of hemolytic and nonhemolytic subcategories of PLS is recommended. When feasible, an antibody screen performed on the donor's plasma when collecting the hematopoietic stem cells or before an organ harvest could result in an alert that the donor has formed an alloantibody(s) and the recipient is a risk for PLS. Alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…The incidence of biochemically evident passenger lymphocyte syndrome in liver transplantation is reported to be up to 40%; however, less than 30% of these cases will demonstrate clinically significant haemolysis requiring intervention 7–9. Less than 20 published studies have reported passenger lymphocyte syndrome following liver transplantation 4 5 8 10–26. Most cases were in the setting of minor ABO mismatch followed by Rh incompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of biochemically evident passenger lymphocyte syndrome in liver transplantation is reported to be up to 40%; however, less than 30% of these cases will demonstrate clinically significant haemolysis requiring intervention 7–9. Less than 20 published studies have reported passenger lymphocyte syndrome following liver transplantation 4 5 8 10–26. Most cases were in the setting of minor ABO mismatch followed by Rh incompatibility.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinic, the transfusion of incompatible RBCs causes specific alloantibodies, thereby leading to intravascular or extravascular haemolysis, which leads to the aggravation of anaemia symptoms and threatens the lives of patients [61][62][63]. Preventing or minimizing alloimmunization will improve the efficacy of erythrocyte transfusion and avoid adverse transfusion reactions [64][65][66]. DCs or their precursors have the ability to distinguish between self and allogeneic non-self as they would between self and microbial non-self -a phenomenon referred to as 'innate allorecognition' [67].…”
Section: Discussionmentioning
confidence: 99%
“…Es gibt Hinweise in der Literatur, dass Lymphozyten aus dem Transplantat auch Antikörper gegen Blutgruppenmerkmale bilden können, die beim Empfänger nicht vorhanden sind. Die Autoren sprechen da von einem "nicht hämolytischen PLS", das lediglich von immunologischem Interesse ist, aber praktisch keine klinische Bedeutung aufweist [30].…”
Section: Immunhämatologische Komplikationen Bei Ab0-minor-inkompatibiunclassified